THE CONTROL AND MANAGEMENT OF RAW MATERIAL RESOURCES IN MAINTAINING THE PRODUCTION DIVISIONS OF BANANA CAKRA BAWANA PASURUAN - Mukayati Mukayati (NAROTAMA UNIVERSITY, Indonesia)
Every company either a service company or a manufacturing company must have the same goal of earning profit. But to achieve that goal is not easy because it is influenced by several factors, and the company must be able to handle these factors. One of the factors that affect the problem is the smoothness of production. The production problem is a very important problem for the company because it is very influential on the profits obtained by the company. If the production process runs smoothly then the company's goal can be achieved, but if the production process does not run smoothly then the company's goals will not be achieved. While the smoothness of the production process itself is influenced by the presence or absence of raw materials will be processed in production.